Trends in Scientific Publications on The Relationship Between Emotional Intelligence, Burnout, and Nurses' Turnover Intention: A Bibliometric Analysis 2012–2024 - Sinollah; Sudarmiatin; Agus Hermawan (International Journal of Economics, Business and Innovation Research, 2025)
Emotional intelligence (EI) has emerged as a critical psychological resource influencing nurses’ resilience, job satisfaction, and intention to remain in the profession. However, research connecting EI, burnout, and turnover intention among nurses remains fragmented, lacking a comprehensive synthesis of global trends and policy implications. This study aims to map the evolution, thematic structure, and research collaboration patterns of scientific publications on the relationship between emotional intelligence, burnout, and nurses’ turnover intention from 2012 to 2024, using bibliometric analysis as an integrative approach. Data were retrieved from Scopus and Web of Science databases using Boolean search strategies. A total of 528 articles were analyzed using VOSviewer (v1.6.20) and Biblioshiny (R/Bibliometrix) to identify performance indicators, co-authorship networks, keyword co-occurrence, and thematic evolution. The study also assessed the linkage between research trends and public policy development in nursing workforce management. The findings reveal a substantial increase in publications after 2020, primarily driven by the COVID-19 pandemic’s impact on nurses’ emotional well-being. Four major thematic clusters were identified: (1) emotional intelligence and resilience, (2) burnout and coping, (3) turnover intention and retention, and (4) health policy and mental well-being. The USA, China, and South Korea emerged as the top contributors, while Frontiers in Psychology and Journal of Nursing Management were the leading publication outlets. Research on EI–burnout–turnover intention has evolved from individual-level psychological inquiry to policy-oriented organizational frameworks. The integration of emotional intelligence into workforce policies and leadership models is crucial for sustaining nursing retention and mental health resilience